Efficacy and acceptability of early mifepristone-misoprostol medical abortion in Ukraine: Results of two clinical trials. (April 2013) - Raghavan, Sheila; Maistruk, Galina; Shochet, Tara; Bannikov, Vladimir; Posohova, Svetlana; Zhuk, Svetlana; Lishchuk, Vladimir; Winikoff, Beverly
ABSTRACT Background Abortion services are legally available in Ukraine although there are issues in quality and access. Two studies were conducted in Ukraine to expand options for women, and to determine the efficacy and acceptability of medical abortion. Study design Two open-label clinical trials were conducted at six clinics in Ukraine. Women were given 200 mg mifepristone followed after 48 hours by 400 μg oral misoprostol (Study One) and mifepristone followed after 24 hours by 400 μg sublingual misoprostol (Study Two). Follow-up visits were scheduled for two weeks after mifepristone administration to assess whether complete uterine evacuation had occurred. Results Success rates were 97% in the first study and 98% in the second one. The vast majority of participants were satisfied or very satisfied with their abortion method (Study One: 94%; Study Two: 98%). Conclusions The two studies demonstrate high rates of success and acceptability of early medical abortion in Ukraine.